1981
DOI: 10.1111/j.1600-0722.1981.tb01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status of 14–16‐year‐old Danish schoolchildren

Abstract: – The purpose of this study was to determine the prevalence of periodontal disease in teenagers. The survey was conducted on 325 children aged 14,15 and 16 years, living in Aarhus, Denmark. Pocket depth and loss of attachment were measured in mm at the maxillary and mandibular first molars and incisors. Plaque, calculus and gingival bleeding on probing were recorded. A total of 221 children (68%) had 4–5 mm deep pockets and 19 children (5.8%) had pockets deeper than 5 mm on at least one tooth Approximately 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
3
24
0
1
Order By: Relevance
“…In young adults, a wide range in the prevalence of sites with a distance > 2 mm from the cementoenamel junction to the alveolar crest has been reported (1–89%) (80). The large variations in radiographic results among studies may be due to methodologic problems, but also to differences in the race of study subjects, their disease susceptibility and access and use of preventive care (1, 2, 5, 11, 17, 40, 52, 59, 66, 67, 81, 82, 155). Adolescents not performing oral preventive measures showed more loss of crestal alveolar bone than adolescents enrolled in a preventive care program (80).…”
Section: Radiographic Parameters Obtainable In Daily Dental Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In young adults, a wide range in the prevalence of sites with a distance > 2 mm from the cementoenamel junction to the alveolar crest has been reported (1–89%) (80). The large variations in radiographic results among studies may be due to methodologic problems, but also to differences in the race of study subjects, their disease susceptibility and access and use of preventive care (1, 2, 5, 11, 17, 40, 52, 59, 66, 67, 81, 82, 155). Adolescents not performing oral preventive measures showed more loss of crestal alveolar bone than adolescents enrolled in a preventive care program (80).…”
Section: Radiographic Parameters Obtainable In Daily Dental Practicementioning
confidence: 99%
“…Studies evaluating initial crestal alveolar bone loss have proposed different thresholds to distinguish between disease and no disease: > 1 mm (71, 90, 95), > 1.5 mm (34), > 2 mm (66, 67, 86) or > 3 mm (18, 88). The choice of cutoff values affects the diagnostic sensitivity and specificity in detecting alveolar bone loss.…”
Section: Radiographic Parameters Obtainable In Daily Dental Practicementioning
confidence: 99%
“…There is great variability among studies conducted in different countries. In Western European countries, in which white populations were examined, the prevalence was between 0.1% and 0.2% 7,15,16,19,20 . The prevalence was reported to be 0.1% in England, 21 0.6% in The Netherlands, 22 and 0.3% to 2.4% in various parts of the United States, 2,8,23‐25 where the study populations were of mixed ethnic origins.…”
Section: Discussionmentioning
confidence: 92%
“…Variations in the gender ratio have also been attributed to age differences in the study populations 15 . In general, more recent epidemiologic studies 5,8,15,16 of random samples with well‐defined diagnostic criteria did not confirm a higher prevalence in females. Saxby 10 suggested that the gender ratio for the disease might be more balanced than previously supposed.…”
mentioning
confidence: 99%
“…In addition, there have been some cross-sectional studies in which caries prevalence has been recorded at 5-to 10-yr intervals (2)(3)(4)(5), As most of these epidemiologic studies have concentrated on dental caries, knowledge of a corresponding improvement in periodontal health is much scarcer. Recently, however, prevalence studies of gingival and periodontal status have been published (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%